Cortisol-induced SRSF3 expression promotes GR splicing, RACK1 expression and breast cancer cells migration. (May 2019) - Buoso, Erica; Ronfani, Melania; Galasso, Marilisa; Ventura, Denise; Corsini, Emanuela; Racchi, Marco
Graphical abstract: Abstract: Recent data have demonstrated that triple negative breast cancer (TNBC) with high glucocorticoid receptor (GR) expression are associated to therapy resistance and increased mortality. Given that GR alternative splicing generates mainly GRα, responsible of glucocorticoids action, we investigated its role in the regulation of RACK1 (Receptor for Activated C Kinase 1), a scaffolding protein with a GRE (Glucocorticoid Response Element) site on its promoter and involved in breast cancer cells migration and invasion. We provide the first evidence that GRα transcriptionally regulates RACK1 by a mechanism connected to SRSF3 splicing factor, which promotes GRα, essential for RACK1 transcriptional regulation and consequently for cells migration. We also establish that this mechanism can be positively regulated by cortisol. Hence, our data elucidate RACK1 transcriptional regulation and demonstrate that SRSF3 involvement in cells migration implies its role in controlling different pathways thus highlighting that new players have to be considered in GR-positive TNBC.